Forestry and economic development - Sartorius, Peter; Henle, Hans V. (New York : Praeger, 1968)
The authors in this book attempt to explain in terms beyond strictly sectoral analysis and technical recordings of the role of forestry in present-day rural economics and social affairs and to summarize its impact on world-wide development efforts. The volume also attempts to show some of the consequences that modern sustained-yield forestry may have upon social environment in the largest sense of the term.
Bibliography: p. 327-337.
rpm 22/01/2019
Loans
Keywords: Forests and forestry; Forest policy